Edoardo Ongaro, Public Management Reform and Modernization. Trajectories of administrative change in Italy, France, Greece, Portugal and Spain, Edward Elgar, Cheltenham 2009, 316 σελ. - Σπανού, Καλλιόπη (Ελληνική Επιθεώρηση Πολιτικής Επιστήμης, 2017)
Δεν διατίθεται περίληψη / no abstract available